Thinking rhythm objects - Godøy, Rolf Inge (Frontiers in Psychology, 2022)
The focus of this mini review is on rhythm objects, defined as strongly coherent chunks of combined sound and body motion in music, typically in the duration range of a few seconds, as may for instance be found in a fragment of dance music, in an energetic drum fill, in a flute ornament, or in a cascade of sounds of a rapid harp glissando. Although there has been much research on rhythm in continuous musical sound and its links with behavior, including the neurocognitive aspects of periodicity, synchrony, and entrainment, there has been much less focus on the generation and perception of singular coherent rhythm objects. This mini review aims to enhance our understanding of such rhythm objects by pointing to relevant literature on coherence-enhancing elements such as coarticulation, i.e. the fusion of motion events into more extended rhythm objects, and intermittent motor control, i.e. the discontinuous, point-by-point control and triggering of rhythm objects.